Shear-wave elastography of the testicle: potential role of the stiffness value in various common testicular diseases. Issue 7 (July 2020) - Roy, C.; de Marini, P.; Labani, A.; Leyendecker, P.; Ohana, M.
Abstract : AIM: To assess the value and efficacy of real-time shear-wave elastography (SWE) of normal testicular parenchyma and various common testicular diseases in clinical practice. MATERIALS AND METHODS: SWE was undertaken in 338 patients (mean age: 43.2±17.2 years, range 17–78 years) comprising normal testicles ( n  = 358), testicular microlithiasis ( n  = 40), and various testicular diseases ( n  = 208) and the stiffness was recorded. The final diagnosis was correlated with the clinical context, long-term follow-up, or histopathology. Statistical evaluation was performed to provide a stiffness threshold for pathological diagnosis. RESULTS: The mean size of testicular lesions was 2.6±1.5 cm (range: 10–42 mm). The mean Young's modulus value for normal testis was recorded at 4.55±2.54 kPa. Whatever the stage of microlithiasis, a higher statistically significant stiffness value was recorded. For acute orchitis, the mean stiffness value was slightly higher, but not statistically significantly. The testicular tumoural processes presented a median stiffness value of 21.02 kPa with a cut-off of 16.1 kPa. Fibrosis presented the highest median stiffness value of 30.03 kPa with a cut-off of 26.3 kPa. By analysing the distribution of the different pathological groups, the difference was statistically significant between fibrosis and tumoural processes ( p  = 0.001). CONCLUSION: SWE is a feasible technique in the exploration of the testicular parenchyma. SWE values can be used to differentiate testicular fibrosis from a tumoural process with confidence. Highlights: Real-time SWE is a feasible technique in the exploration of testicular parenchyma. SWE is not a time consuming process without impact on the workflow. The stiffness value can be used to distinguish fibrosis from a tumoral process. The reference for normal value is dependent of the type of elastography software.